POLITIK KEKERABATAN DI PILKADA: STUDI KASUS TERPILIHNYA PASANGAN CALON HJ. SRI HARTINI S.E – HJ. SRI MULYANI PADA PILKADA KABUPATEN KLATEN TAHUN 2015 - Catur Puguh Pamungkas; Laila Khalid Alfirdaus; Priyatno - Harsasto (Journal of Politic and Government Studies, 2018)
The issues of palace politics emerge along with the candidacy of Sri Hartini – Sri Mulyani as a candidate for Regent and a candidate for Vice Regent of Klaten Regency. The candidate candidacy is associated with the palace politics because the figures have a marriage bond with the previous ruler. The implementation of the election regency of Klaten was won by Sri Hartini-Sri Mulyani’s partner with the acquisition of 321.593 votes or 54.39% of the valid ballots. There are figures that influence the palace politics in the election that is Sunarna as the Chairman of PDIP DPC Klaten Regency and the local ruler. The winner of the palace politics is closely linked to the political culture of neo-patrimonialism involving the patron-client relationship and governmental authority.The purpose of this study is to analyze how the palace politics work in winning candidate pairs in the election regency. The palace politics in winning a candidate cannot be separated from the candidate’s figuration, the strength of the political party, and the relationship of palace politics with neo-patrimonialism culture. The method of the study is the qualitative explorative, in which the primary data from this study is obtained directly from interviewing activity with the resource while the secondary data is obtained indirectly through documents, mass media, internet, and other literary studies. Furthermore, the writer examines the data with the data obtained to draw the conclusion and verification of the data. Thus, it produces the descriptive data, which is to describe the results of the analysis of how the palace politics work in the election regency.Keywords: Election of Regent, Local Democracy, Palace Politics, Neo-Patrimonialism.